The rights of temporary occupation license holders under The National Land Code, 1965: a comprehensive study / Zawawi Kamaruzzaman - Kamaruzzaman, Zawawi (Faculty of Law, 1986)
Before the introduction of Torrens System in Malaya, not a single system of land registration exist. Noticeably, during the pre—colonial days in the Malay States, land was given to anyone who could develop it. To this verbal licences to occupy the Land were granted and documentary permits to enter the land were freely issued. This is an early Form of the Malay's customary tenure of land. There are two types of adat or customary law in Peninsula Malaysia that is, Adat Perpateh and Adat Temenggong. Adat Perpateh is the personal law of those Malays living For the most part Negeri Sembilan and Malacca, who are the descendants of the Minangkabau race of Sumatera, observe matriarchal rules. Adat Temenggong Malays are those descended from the people of Palembang but who follow patriarchal rules.